Bebtelovimab-Induced Bradycardia Leading to Cardiac Arrest. (19th August 2022) - Gearges, Christina; Haider, Hibah; Rana, Vishal; Asghar, Zahra; Kewalramani, Anjali; Kuschner, Zachary
Abstract : BACKGROUND: Bebtelovimab is a monoclonal antibody used to prevent progression of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Complications of SARS-CoV-2 infection can include cardiac effects including sinus bradycardia. CASE SUMMARY: We describe the case of an 86-year-old male infected with SARS-CoV-2 who experienced bradycardia with cardiac arrest immediately following infusion of Bebtelovimab with return of spontaneous circulation obtained following 1 minute of chest compressions and administration of atropine. His bradycardia resolved, and he was extubated on hospital day 1, found to be neurologically intact, and discharged on hospital day 9. CONCLUSIONS: Due to the time course of the patient's symptomatology, we attribute the bradycardic arrest to the Bebtelovimab infusion. This case illustrates the need for further research into the etiology of bradycardia due to SARS-CoV-2 infection and to examine potential links to monoclonal antibody infusion. It also serves as important caution to maintain close cardiac monitoring while administering monoclonal antibodies for SARS-CoV-2.